Asymptomatic bacteriuria in type II diabetics and non-diabetics; risk factors, bacterial types and their corresponding resistance pattern - Abujheisha, khalil (My University, 2019)
Introduction: Silent bacteriuria or asymptomatic bacteriuria (ASB) means the existence of bacteria in urine without clinical signs or symptoms of the host. Asymptomatic bacteriuria is considered clinically significant and worth treating primarily in pregnant women. Objectives: In this study, we examined the silent bacteriuria among diabetics and healthy persons, type of strains, and their corresponding resistance pattern. Materials and Methods: A total of 220 diabetic patients and 70 healthy persons were subjected to study. Diabetic patients without malignancies, asthma or heart diseases, symptoms free regarding urinary tract infection and without prior antibiotic administration were included. Blood samples were obtained from all subjects under aseptic technique for fasting blood sugar and HbA1c. Urine samples were collected. All urine samples were passed to cultivation on suitable culture media. Plates of more than two clinical isolates from the same patient were considered to be contaminated. Plates showing more than 104 CFU/mL were considered significant ASB and subjected for confirmation of bacterial type and antibiotic susceptibility test. Results: From diabetics urine samples, 21 (9.55%) and from healthy persons 3 (4.3%) showed significant bacterial growth. In both diabetics and non-diabetics, women demonstrated a far higher prevalence of ASB than men. The high the HbA1c, the more possibility of positive ASB. In 66.7% of ASB, E. coli was the main uropathogens, followed by K. pneumoniae. These species showed identical antibiotic resistance patterns. Conclusion: These findings emphasize the importance of routine urine culture and antibiotic sensitivity testing for diabetic patients who have identified risk factors. ASB should be treated to avoid potential serious renal complications. Amikacin, gentamicin, piperacillin/tazobactam, fosfomycin, and ciprofloxacin are recommended for treatment of ASB while ampicillin is not.
Keywords: Diabetes mellitus Asymptomatic bacteruria E. coli Antibiotics Urinary tract infection Extended spectrum beta lactamase